2016
DOI: 10.3389/fpls.2016.00862
|View full text |Cite
|
Sign up to set email alerts
|

The Aquaporin Splice Variant NbXIP1;1α Is Permeable to Boric Acid and Is Phosphorylated in the N-terminal Domain

Abstract: Aquaporins (AQPs) are membrane channel proteins that transport water and uncharged solutes across different membranes in organisms in all kingdoms of life. In plants, the AQPs can be divided into seven different subfamilies and five of these are present in higher plants. The most recently characterized of these subfamilies is the XIP subfamily, which is found in most dicots but not in monocots. In this article, we present data on two different splice variants (α and β) of NbXIP1;1 from Nicotiana benthamiana. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 65 publications
(120 reference statements)
2
31
0
Order By: Relevance
“…After their discovery and the observation that this subfamily was lost in monocots and in some dicots such as the Brassicacea (Danielson & Johanson, 2008), XIP isoforms have been identified and their expression profile under different growth conditions was studied in various plant species (Giovannetti et al, 2012;Lopez et al, 2016;Noronha et al, 2016). Heterologous expression analysis revealed their ability to facilitate the diffusion of small solutes such as glycerol, hydrogen peroxide, urea or boric acid but no or only marginal water permeability (Ampah-Korsah et al, 2016;Bienert et al, 2011;Giovannetti et al, 2012;Lopez et al, 2016). So far, XIP-mediated boric acid permeability was only deduced based on XIP-expressing yeast growth inhibition experiments (Ampah-Korsah et al, 2016;Bienert et al, 2011;Noronha et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After their discovery and the observation that this subfamily was lost in monocots and in some dicots such as the Brassicacea (Danielson & Johanson, 2008), XIP isoforms have been identified and their expression profile under different growth conditions was studied in various plant species (Giovannetti et al, 2012;Lopez et al, 2016;Noronha et al, 2016). Heterologous expression analysis revealed their ability to facilitate the diffusion of small solutes such as glycerol, hydrogen peroxide, urea or boric acid but no or only marginal water permeability (Ampah-Korsah et al, 2016;Bienert et al, 2011;Giovannetti et al, 2012;Lopez et al, 2016). So far, XIP-mediated boric acid permeability was only deduced based on XIP-expressing yeast growth inhibition experiments (Ampah-Korsah et al, 2016;Bienert et al, 2011;Noronha et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The first molecular characterization of plant XIPs demonstrated that NtXIP1;1 from tobacco is localized in the plasma membrane and that its promoter is widely active throughout the plant, both in roots and shoots (Bienert et al., ). In N. tabacum and Nicotiana benthamiana , the transcript of XIP1;1 is spliced in two distinct variants, XIP1;1 α and XIP1;1 β differing in only one amino acid in length (Ampah‐Korsah et al., , ; Bienert et al., ). Toxicity growth assays in the heterologous expression systems Saccharomyces cerevisiae and Pichia pastoris , respectively, suggest that NtXIP1;1α, NtXIP1;1β and NbXIP1;1α function as boric acid channels (Ampah‐Korsah et al., ; Bienert et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed procedure of phosphorylation analysis and dephosphorylation is described in Kinoshita et al 20 with slight modication as mentioned in Ampah-Korsah et al 21 Cloning, expression and purication of human LIP5…”
Section: Dephosphorylation Of Aqp2mentioning
confidence: 99%
“…Since Nb XIP1;1αwt was found in the P. pastoris plasma membrane in a previous study [19], it is likely that the Nb XIP1:1α mutants are also localized to the plasma membrane of P. pastoris and therefore available for functional studies in spheroplasts.…”
Section: Discussionmentioning
confidence: 99%